Development of project based biotechnology teaching books - Hilarius Jago Duda; F Rahayu Esti Wahyuni; Antonius Edy Setyawan; Markus Iyus Supiandi; Yakobus Bustami (Biosfer: Jurnal Pendidikan Biologi, 2022)
Various research states that one of the causes of misconception is textbooks or printed media that are used as learning resources. This is because the textbooks developed are monotonous and tend to present theories in full without practicing skills or stimulating the ability to think and solve problems. The textbooks developed in the research are project-based biotechnology textbooks. This certainly can answer the demands of higher education in the era of industrial revolution 4.0 where learning should be able to empower cognitive, process skills, social skills, system skills, complex problem solving and others. The depth of the material and projects selected for each topic is seen with the results of the analysis of conceptual mastery and misconceptions found. The hope is that this project-based textbook can overcome these problems. The research methodology used is 4-D development research. The 4-D development research method consists of 4 main stages, namely: define, design, develop and disseminate. The subjects of the field trials were biology education students at STKIP Persada Khatulistiwa Sintang. The percentage of validation results for project-based biotechnology textbooks by material experts, media experts, and biotechnology lecturers is 3.75 so that the textbooks have very decent qualifications. The percentage of project validation results was 3.32 with the feasible category. This textbook was tested on biology education students at STKIP Persada Khatulistiwa Sintang at the initial development testing stage. The effectiveness of this textbook is seen from the gain score of 0.54 with moderate criteria, so that it can be declared effective.